PEMBELAJARAN FIQIH THOHAROH ; AKTUALISASI DIRI DAN IMPLEMENTASINYA PADA SISWA MADRASAH TSANAWIYAH MASYARIQUL ANWAR CARINGIN - Hendri, Suhendri; Royhatudin, Aat; Maksudi, Didi; Hidayat, Ahmad; Ahsan Irodat; Masitoh, Imas (Ta'dibiya, 2022)
The learning process of Thoharoh Fiqh is an activity that involves several components, namely educators, students, and other components in the teaching and learning process that influence each other in order to the achievement of predetermined goals is related to important knowledge about the sacred which is a condition for the validity of worship. This study aims to determine the learning process of Thoharoh Fiqh and to know the self-actualization and implementation of students in increasing individual piety at MTs Masyariqul Anwar Caringin through worship practices as a form of individual piety. This research is a field research with a qualitative approach. The subjects in this study were Fiqh teachers and grade VII and VIII MTs Masyariqul Anwar Caringin, while the data in this study were collected through interview, observation, and documentary techniques. The results showed that the Fiqh thoharoh learning process at MTs Masyariqul Anwar Caringin in terms of implementation used the 2013 curriculum, in planning Fiqh teachers also made annual programs, semester programs, syllabus and lesson plans to facilitate the learning process by using methods commonly used at the time of learning, namely the lecture method, demonstration and question and answer. So that the thoharoh practice carried out on MTs Masyariqul Anwar Caringin students is able to practice ablution, tayamum and how to remove najis as a real form of individual piety.